2019
DOI: 10.1159/000504256
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Areas for Improvement in the Management of Bone Metastases in Patients with Neuroendocrine Neoplasms

Abstract: Background: There is no global consensus on the optimal management of bone metastases (BMs) in neuroendocrine neoplasms (NENs). Objectives: To review current management and outcomes of patients with BMs in NENs, in order to identify areas for improvement. Methods: A retrospective study of all patients with NENs, except Grade 3 lung NENs (April 2002 to March 2018) was conducted. Baseline characteristics, nature of BMs, treatment received and overall survival (OS) were evaluated. Statistical analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…In a large retrospective analysis from a part of the US National Comprehensive Cancer Network database including 691 patients, significantly lower survival rates were observed in low-grade NETs arising from both pancreas and small bowel [9]. Similar findings have been reported by other studies performed in ENETS Centers of Excellence across Europe, confirming the negative prognostic impact of bone metastases on patients’ survival [7, 10, 45]. Nevertheless, in a study enrolling 312 consecutive patients with sporadic, grade 1/2, stage IV, nonfunctioning panNETs, the presence of bone lesions predicted a shorter PFS, in the absence of any impact on overall survival [52].…”
Section: Bone Metastases In Nets: Clinical Features Diagnostic Workusupporting
confidence: 63%
See 2 more Smart Citations
“…In a large retrospective analysis from a part of the US National Comprehensive Cancer Network database including 691 patients, significantly lower survival rates were observed in low-grade NETs arising from both pancreas and small bowel [9]. Similar findings have been reported by other studies performed in ENETS Centers of Excellence across Europe, confirming the negative prognostic impact of bone metastases on patients’ survival [7, 10, 45]. Nevertheless, in a study enrolling 312 consecutive patients with sporadic, grade 1/2, stage IV, nonfunctioning panNETs, the presence of bone lesions predicted a shorter PFS, in the absence of any impact on overall survival [52].…”
Section: Bone Metastases In Nets: Clinical Features Diagnostic Workusupporting
confidence: 63%
“…In this regard, an analysis of 85 patients with NETs metastatic to the skeleton showed that bone pain was reported by 28 and 14% of subjects at the initial diagnosis and during the follow-up, respectively [7]. On the other hand, fractures have been described as rare events, occurring in nearly 10–20% of cases, and even lower rates of spinal compression (5%) and hypercalcemia (1–4%) have been reported [7, 45]. Although no clear factor able to predict the development of NET bone metastases has been identified, a correlation with deteriorated performance status has been observed [10].…”
Section: Bone Metastases In Nets: Clinical Features Diagnostic Workumentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study, the NETs that caused skeletal complications are invariably G1 or G2 and this could suggest that bone metastases therapy should therefore be started early also in the less-aggressive types of NET. Preventing skeletal related-events should be one of the primary aims in the treatment process of these patients ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of skeleton health, patients with NENs may suffer from a multitude of factors, not only from direct malignant dissemination to the bone (47,48). For instance, secondary diabetes mellitus due to pancreatic and duodenal tumors such as somatostatinomas (with or without underlying neurofibromatosis type 1), or pheocromocytomas or due to paraneoplastic hypercortisolemia may cause a deterioration of bone quality like that reflected by TBS in addition to abnormal turnover that increase fracture risk (49)(50)(51).…”
Section: Carcinoid-related Osteoporosismentioning
confidence: 99%